Implementasi Matode Weighted Product dalam Penentuan Aplikasi Tatap Muka Pembelajaran Daring - Efori Bu'ulolo; Serta Kurniawan Zega; Viktor Frank Zai (ADA Research Center, 2025)
The development of information technology has encouraged the adoption of online learning systems with various face-to-face applications such as Google Meet, Zoom Meeting, Elearning, Edmodo, and Google Classroom. The diversity of these applications often causes problems in determining the most suitable choice because each application has advantages and disadvantages, both in terms of user capacity, visual interaction, features, application size, and internet data usage. To address these issues, this study implements the Weighted Product (WP) method as a multi-criteria approach capable of providing objective evaluations based on the weight of each criterion's importance. The analysis results show that user capacity is the dominant factor with the highest weight (0.37), followed by visual interaction (0.23) and user-friendly features (0.16), while application size (0.11) and internet data usage (0.07) fall under the cost category. The WP calculation yields preference values that place Elearning (A3) in first place with a value of 0.341, followed by Zoom Meeting (0.241), Edmodo (0.135), Google Meet (0.134), and Google Classroom (0.146). Thus, Elearning is the most optimal application to support online learning, while the WP method has proven to be effective as a decision-making tool in determining the best alternative.